Gastroenteropancreatic Neuroendocrine Neoplasia Characterization in Portugal: Results from the NETs Study Group of the Portuguese Society of Endocrinology, Diabetes and Metabolism - A. P. Santos; J. Vinagre; P. Soares; I. Claro; A. C. Sanches; L. Gomes; I. Fernandes; A. L. Catarino; J. Preto; B. D. Pereira; A. P. Marques; F. Rodrigues; et al. (International Journal of Endocrinology)
Background. The incidence of gastroenteropancreatic neuroendocrine neoplasms (GEP-NENs) has been increasing in the last five decades, but there is no large-scale data regarding these tumours in Portugal. We conducted a cross-sectional, multicentric study in main Portuguese centers to evaluate the clinical, pathological, and therapeutic profile of GEP-NENs. Methods. From November, 2012, to July, 2014, data from 293 patients diagnosed with GEP-NENs from 15 centers in Portugal was collected and registered in an online electronic platform. Results. Median age at diagnosis was 56.5 (range: 15-87) years with a preponderance of females (54.6%). The most frequent primary sites were the pancreas (31.1%), jejunum-ileum (24.2%), stomach (13.7%), and rectum (8.5%). Data regarding hormonal status was not available in most patients (82.3%). Stratified by the tumour grade (WHO 2010 classification), we observed 64.0% of NET G1, 24.7% of NET G2, and 11.3% of NEC. Poorly differentiated tumours occurred mainly in older patients (p=0.017), were larger (p<0.001), and presented more vascular (p=0.004) and lymphatic (p=0.001) invasion. At the time of diagnosis, 44.4% of GEP-NENs presented metastatic disease. Surgery (79.6%) and somatostatin analogues (30.7%) were the most frequently used therapies of GEP-NENs with reported grading. Conclusion. In general, Portuguese patients with GEP-NENs presented similar characteristics to other populations described in the literature. This cross-sectional study represents the first step to establish a national database of GEP-NENs that may aid in understanding the clinical and epidemiological features of these tumours in Portugal.